Keberadaan Kampus II IAIN Ponorogo Dan Dampaknya Terhadap Perekonomian Masyarakat Di Kabupaten Ponorogo - Wida Andina; Kenlies Era Rosalina Marsudi (Institut Agama Islam Negeri Ponorogo, 2023)
Development is a continuous improvement process in society and its social system towards a better standard of living. Development is a change in the level of welfare that is measurable and occurs naturally. The changes affect not only one aspect of life but also fundamental aspects. Changes can be seen in the economic status of the people in the area, like the construction of a higher education institution in a place that will impact changes in its surroundings. The changes that occur are not only the hustle and bustle of activities but also changes in the economic field of the surrounding community because other developments around it will also follow the construction of a higher education institution. So that The main objective of this research is to find out how the influence of the development of higher education institutions has on the economy of the surrounding community. The changes brought about by the establishment of a tertiary institution certainly have an impact on the lives of the surrounding community. The impact in question is an impact that can improve the lives of the surrounding community, especially in the economic sector. The most obvious change is that in the area around the campus, many business establishments have been established, such as boarding houses, restaurants, shops, workshops, laundries, photocopiers, and so on. Establishing these businesses will open up many job opportunities for the community so that the community's economy will also improve. This research is expected to contribute to the development of economic development theory and can be helpful suggestions and references for future research.